2019
DOI: 10.13031/trans.13021
|View full text |Cite
|
Sign up to set email alerts
|

Moisture and Rupture Models for Corn (Zea mays) Seeds of Different Endosperm Types

Abstract: Abstract. Mechanization of postharvest handling and conditioning inflicts damage on the physical, physiological, and sanitary qualities of corn (Zea mays) seeds, resulting in significant economic loss. The mechanical damage is related to the compression strength and strain, and therefore to the moisture content (MC) and endosperm type. This study was conducted from 2012 to 2014 at the Montecillo and Chapingo agricultural institutes in Mexico, where physical properties such as volumetric weight; apparent densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Rupture force was defined as the force required to produce a major break in the kernel. Previous research has shown that unfermented kernels had lower rupture force as kernel moisture content increased [7,8,13,22]. Rupture force was statistically less for the F-Low and F-High fermented kernels than for the U-Low and U-Mid kernels (Table 8).…”
Section: Discussionmentioning
confidence: 81%
“…Rupture force was defined as the force required to produce a major break in the kernel. Previous research has shown that unfermented kernels had lower rupture force as kernel moisture content increased [7,8,13,22]. Rupture force was statistically less for the F-Low and F-High fermented kernels than for the U-Low and U-Mid kernels (Table 8).…”
Section: Discussionmentioning
confidence: 81%
“…Tis is because, under conditions of high moisture content, the endosperm cells in the grain will absorb water and fll the internal voids, making the grain structure expand. Tis not only afects the physical properties of grains, such as 1000-grain weight, bulk density, and true density, but also makes the endosperm texture softer, which in turn reduces the mechanical strength of the grain [97]. Te microstructure of oats was diferent under diferent water contents.…”
Section: Moisture Contentmentioning
confidence: 99%